Incidence and outcomes of delayed presentation and surgery in peritoneal surface malignancies - Tan, Jun Kiat Thaddaeus; Wong, Jolene Si Min; Seo, Chin Jin; Lim, Cindy; Zhu, Hong-Yuan; Ong, Chin-Ann Johnny; Chia, Claramae Shulyn (Frontiers in Oncology, 2023)
BACKGROUND Peritoneal surface malignancies (PSM) present insidiously and often pose diagnostic challenges. There is a paucity of literature quantifying the frequency and extent of therapeutic delays in PSM and its impact on oncological outcomes. METHODS: A review of a prospectively maintained registry of PSM patients undergoing Cytoreductive Surgery and Hyperthermic Intra-peritoneal Chemotherapy (CRS-HIPEC) was conducted. Causes for treatment delays were identified. We evaluate the impact of delayed presentation and treatment delays on oncological outcomes using Cox proportional hazards models. RESULTS: 319 patients underwent CRS-HIPEC over a 6-years duration. 58 patients were eventually included in this study. Mean duration between symptom onset and CRS-HIPEC was 186.0 ± 37.1 days (range 18-1494 days) and mean duration of between patient-reported symptom onset and initial presentation was 56.7 ± 16.8 days. Delayed presentation (> 60 days between symptom onset and presentation) was seen in 20.7% (n=12) of patients and 50.0% (n=29) experienced a significant treatment delay of > 90 days between 1st presentation and CRS-HIPEC. Common causes for treatment delays were healthcare provider-related i.e. delayed or inappropriate referrals (43.1%) and delayed presentation to care (31.0%). Delayed presentation was a significantly associated with poorer disease free survival (DFS) (HR 4.67, 95% CI 1.11-19.69, p=0.036). CONCLUSION: Delayed presentation and treatment delays are common and may have an impact on oncological outcomes. There is an urgent need to improve patient education and streamline healthcare delivery processes in the management of PSM.